Effectiveness and tolerability of perampanel in сhildren and adolescents (own experience of Svt. Luka’s Institute of Child Neurology and Epilepsy) - K. Y. Mukhin; O. A. Pylaeva; M. Y. Bobylova (Русский журнал детской неврологии, 2022)
Despite the significant advances in epileptology, including various new effective treatments for drug-resistant epilepsy in children, there is still a relatively large proportion of patients ineligible for surgery and alternative treatments (such as vagus nerve stimulation and ketogenic diet). Drug-resistant epilepsy accounts for approximately 30 % of all forms of epilepsy and is particularly common among patients with focal seizures. The search for new antiepileptic drugs (AEDs) is critical for these patients.Perampanel (Fycompa®, Eisai) is a novel AED that employs a fundamentally different mechanism of action compared to existing AEDs. Perampanel is a powerful highly selective non-competitive postsynaptic AMPA receptor antagonist acting at the level of neocortex and in the hippocampus. Phase III clinical trials demonstrated its high efficacy and good tolerability in patients with drug-resistant focal seizures. Randomized placebo-controlled trials assessing the efficacy of perampanel as add-on therapy showed that perampanel at a dose of 4–12 mg/day significantly reduced the frequency of focal seizures in patients with drug-resistant epilepsy along with a good safety and tolerability profile.Open-label observational studies and studies analyzing long-term therapy also demonstrated high efficacy and safety of long-term treatment with perampanel (up to 3 years), as well as good retention rate. The drug has a once-daily dosing schedule, which is very comfortable for patients.In 2012, perampanel (Fycompa®) was approved for epilepsy patients in the USA and Europe. In 2013, it was approved in Russia as an add-on therapy for patients aged 12 years and older with focal and secondary generalized seizures. On 29.06.2015, it was also approved for polytherapy of generalized tonic-clonic seizures in patients aged 12 years and older with idiopathic generalized epilepsy.On 07.12.2020, perampanel was approved for children aged 4 years and older (body weight >30 kg) as a part of polytherapy for focal and secondary generalized seizures and for children aged 7 years and older with idiopathic generalized epilepsy as a part of polytherapy for generalized tonic-clonic seizures.Currently, there is limited evidence of perampanel efficacy in children in Russia.The study aimed to evaluate the efficacy and tolerability of perampanel in children (aged 4–11 years) and adolescents (aged 12–18 years) with epilepsy treated and followed-up at Svt. Luka’s Institute of Child Neurology and Epilepsy.Materials and methods. This study included 136 patients (aged 4–18 years; 75 males and 61 females) who received perampanel and were followed-up for at least 6 months at our institution. Patients were divided into two groups: children (aged 4–11 years; n = 105) and adolescents (aged 12–18 years; n = 31).The following types of epilepsy were diagnosed in study participants: structural focal epilepsy (n = 60), genetic epilepsy (n = 61; including Dravet syndrome, Angelman syndrome, Lafora disease, mutations in the PCDH19, PHACTR1, CDKL5, ARX, PING, SCN2A, KIAA2022 genes, chromosome microdeletions, etc.), focal epilepsy of unknown etiology (n = 12), idiopathic epilepsy (n = 3). In all cases, perampanel was used as an additional AED, often in combination with valproic acid. Dose adjustment was performed according to the package insert (by increments of 2 mg either weekly or every 2 weeks) up to a therapeutic dose of 4–12 mg/day at bedtime.Results. In children (aged 4–11 years; n = 105), seizure remission was achieved in 29 cases (27.6 %). Fifty-five children (52.4 %) had ≥50 % efficacy, whereas 17 children (16.2 %) had <50 % reduction in seizure frequency or no effect. Four patients (3.4 %) reported aggravation of seizures. A significant therapeutic effect (remission or at least 50 % reduction in seizure frequency) was registered in 84 out of 105 patients (80 %). Parents of 23 children also reported better development and improved skill acquisition along with a reduced frequency of seizures (in 34 % of 67 children with cognitive disorders). Parents of 8 children who had sleeping difficulties (trouble falling asleep, restless sleep, frequent awakenings) reported an improvement of sleep.Among adolescents (n = 31), we observed the following parameters of treatment efficacy: 9 of them (29 %) achieved seizure remission; 15 patients (48.4%) had 50 % efficacy; 6 patients (19.4 %) had <50 % reduction in seizure frequency or no effect; one patient (3.2 %) had seizure aggravation. Thus, good therapeutic effect (remission or at least 50 % reduction in seizure frequency) was achieved in 24 out of 31 patients (77 %).Therapy with perampanel was effective (remission or at least 50 % reduction in seizure frequency) in 108 out of 136 patients aged 4–18 years (79.4 %). The overall seizure remission rate reached 27.9 % (38 out of 136 patients).The inclusion of perampanel into polytherapy resulted in suppression of epileptiform activity on the electroencephalogram (EEG) or in a significantly reduced index of epileptiform activity in 38 out of 112 patients who underwent followup EEG examination (i.e. in more than one-third of cases).Adverse events were registered in 41 patients out of 136 (30.1 %).Perampanel was discontinued in 15 out of 136 patients (11 %) due to tolerability issues primarily because of psychiatric adverse events (5.9 % from the total number of patients).The 12-month retention rate in children and adolescents was 78.7 % (107 out of 136 patients).Conclusion. Perampanel was highly effective in children and adolescents with genetic and structural focal epilepsy. The drug has a convenient once-daily dosing schedule with slow titration and is well tolerated by patients during longterm therapy. Our results demonstrate that perampanel is also effective in children below 12 years of age, even at a dose of 2–4 mg/day; it is well tolerated and is comfortable for use. Its efficacy and tolerability did not differ significantly between children and adolescents. Our findings suggest that perampanel is highly effective in patients with some forms of genetic epilepsy.Perampanel should be used not only for drug-resistant epilepsy, but also as the first additional drug in combination therapy for epilepsy, since it is likely to improve treatment efficacy and ensure better tolerability.